The uncertainty evaluation method of supply chain reliability - Miao, Xin; Yu, Bo; Xi, Bao (Transport, 2009)
The objective of the article is to scientifically evaluate supply chain reliability (SCR). We argue that this problem relates to two aspects ‐ the cognition and expression of SCR. The paper considers SCR as a unification of a fuzzy and random meaning in a dynamic environment. Furthermore, intrinsic relationship between the theoretical foundation of SCR evaluation and the cloud theory is discovered, accordingly to which, the cloud theory is applied to study the evaluation of SCR from a holistic perspective. According to the comprehensive invalidation degree of a supply chain, SCR is differentiated as six grades and the influencing factors of SCR are classified taking into account __ve aspects. A comprehensive performance model is developed to measure five aspects of influencing factors and to evaluate the exact class SCR belongs to. As we know, the cognition of SCR depends on human mind while the natural language is an appropriate medium to express human mind. Therefore, linguistic terms are adopted to express uncertain transformation between qualitative concepts and their corresponding quantitative values. This method is further demonstrated using a numerical example.First published online: 27 Oct 2010